ARE UNIVERSITIES ABLE TO USE THE POTENTIAL OF STUDENTS – DIGITAL NATIVES? - Butrimė, Edita; Zuzevičiūtė, Vaiva; Vitkutė-Adžgauskienė, Daiva (Verbum, 2015)
The research idea was formulated when the learning achievements of first-year students were analyzed. An empirical study revealed that first-year students (Digital Natives (DN)) are quite reluctant to leave the comfort zones of Facebook and similar social networks in order to explore learning possibilities embedded in other platforms, including the ones provided by a university. This paper is based on theoretical and empirical research. Experience collected from three different universities raised concerns addressed in designing and carrying out the study based on qualitative and quantitative research methodology; however, due to limitations of this paper, only pilot study results are presented. Problem questions are formulated in the context where students (DN) apply information and communication technology (ICT) based tools in their everyday (leisure) activities (hence, it is attractive to them). Why then are the ICT based tools used specifically for virtual learning environments not attractive? How students evaluate the environment for communication and group work at university? The aim of the study is to identify the perspective of students (specifically, not students of information sciences) on ICT based tools and their application for studies. Conclusions: the issue of students (DN) not using the opportunities of the Internet (or ICT) based tools for their own learning during studies is, if not universal, then, surely, wide spread; students really sometimes fail to conceptualise ICT tools being useful for learning, and they really do not conceptualise university having a virtual subsidiary (virtual study-platform) as an integral part of a given university; the role of a teacher, at least for some time now and into the future, remains important and significant.
Keywords: e-learning of university students; learning of Digital Natives; ICT based learning tools; Web 2.0 based learning tools